Allostatic load and reduced cortical thickness in schizophrenia. (March 2017) - Chiappelli, Joshua; Kochunov, Peter; Savransky, Anya; Fisseha, Feven; Wisner, Krista; Du, Xiaoming; Rowland, Laura M.; Hong, L. Elliot
Highlights: Schizophrenia patients had significantly higher levels of an index of allostatic load compared to healthy controls; this difference partially accounted for lower cortical thickness observed in patients compared to controls. C-reactive protein was the only component of the allostatic load index inversely correlated with cortical thickness in both patients and controls independently. Further work necessary to identify the extent to which elevated allostatic load in schizophrenia patients is due to stress versus antipsychotic medication and lifestyle changes. Abstract: Structural imaging studies have consistently found reduced gray matter thickness of the cerebral cortex in schizophrenia, a finding that is evident in first episode psychosis and may be progressive in some cases. Although genetic predisposition and medication effects may contribute to cortical thinning, we hypothesize that the cumulative effects of stress may represent an environmental factor impacting brain morphology in schizophrenia. We examined the relationship between allostatic load, an index of peripheral biomarkers representing the cumulative effects of stress, and cortical thickness. Allostatic load was calculated for 44 patients with schizophrenia spectrum disorders (SSD) and 33 normal controls (NC) based on 13 cardiovascular, neuroendocrine, immune, and metabolic measurements. Controlling for age, SSD had significantly elevated allostatic load as compared with NC (p = 0.008). Controlling for age, whole brain average cortical thickness was lower in SSD patients compared to NC (p = 0.008). However, once allostatic load was accounted for, the group difference in cortical thickness became marginal (p = 0.058). Exploratory analyses on subcomponents of allostatic load suggested that elevated immune marker C-reactive protein, stress hormones, and cardiovascular indices within allostatic load were more strongly associated with reduced cortical thickness in SSD. In NC, only the association between immune marker C-reactive protein and cortical thickness was replicated. These results support the hypothesis that allostatic load may account for some of the gray matter deficits observed in schizophrenia. Among the allostatic indices, the inflammatory mechanism appears particularly relevant to cortical thickness in both schizophrenia patients and normal controls.